A Preliminary Silvical Study on Acacia Tortilis (forsk) Hayne (Acacia Spirocarpa Hochst. Ex A. Rech) - Kaul, R. N. (Indian Forester, 1963)
The genus Acacia contains over 20 Indian and some introduced species, the three most important of the latter being of Australian origin, namely, A. decurrens, A. dealbata. And A. melanoxylon (Troup, 1921). Arboreta trials conducted over a period of four years at Pali and Jodhpur in Rajasthan have indicated the possibility of adding Acacia tortilis (Forsk) Hayne (Acacia spirocarpa Hochst ex A. Rech) from Israel to the existing list of exotic Acacias as a promising tree species for the arid and semi arid zones of India.